The experiences of newly diagnosed men who have sex with men entering the HIV care cascade in Lima, Peru, 2015-2016: A qualitative analysis of counselor-participant text message rxchanges - Bayona, Erik (2017)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.